Intervensi Virtual Reality dalam Mengatasi Kecemasan Pada Pasien Pencabutan Gigi - Priyambodo, R. Ardian; Liasari, Ira; Purwanti, Uzy; Jumriani (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2022)
Anxiety that is directly related to dental treatment, including tooth extraction, is still a problem experienced by many people around the world. Therefore, various methods have been developed to overcome this anxiety problem. Virtual reality is one of distraction method that often gets attention in medical context lately. Virtual reality uses advanced technology to create a virtual environment that immerses the patient in an interactive simulated world. This study aims to determine the effect of virtual reality interventions on patient anxiety during tooth extraction procedures at Haji Makassar General Hospital. This type of research is a clinical experimentalstudy with a pre test and post test research design with a control group design. The results showed that after the virtual reality intervention, there were average decreases in systolic blood pressure (6%), respiratory rate (9%), and pulse rate (12%). Whereas in the control group there were average increases in systolic blood pressure (2%), respiratory rate (3%), and pulse rate (4%). So it can be concluded that virtual reality intervention can reduce patient anxiety before tooth extraction procedure.